Demographic characteristics and problem areas of U.P. College of Agriculture freshmen - Simpas, Carmencita S. 1939- (s.n.], 1971)
This study presented a survey of the demographic characteristics and problem areas of the 1970 University of the Philippines College of Agriculture freshmen through these instruments: the background information sheet and the money problems checklist. Certain demographic characteristics were tested for significant relationships. Tests for correlation were made among sex, age, regional origin, major areas and